2011
DOI: 10.1080/02607476.2011.611017
|View full text |Cite
|
Sign up to set email alerts
|

Searching high and searching low, searching east and searching west: looking for trust in teacher education

Abstract: This paper considers what has been learned from reviewing the full set of papers in this special issue. It considers some of the major factors that have impacted on education, and subsequently teacher education in recent times, namely rapid technological change and increasing globalisation and movement from one country to others and then focuses on how standards, for schools, for the people in them and for teacher education, have been used to drive improvement in many parts of the world. Key issues that have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Teacher's work is multidimensional and complex and the teacher plays a number of different and challenging roles: instructional manager; caring person; and, generous expert learner and cultural and civic person (Conway, Murphy, Rath, & Hall, 2009). Analysing the role of the teacher in six countries, Duda and Clifford-Amos Taking an international perspective, Townsend (2011) suggested that from the policy, research and practice points of view, ITE stakeholders are "on a quest" in an era of increasing accountability framed by conditions when:…”
Section: Reconsidering the Teacher Education Curriculummentioning
confidence: 99%
“…Teacher's work is multidimensional and complex and the teacher plays a number of different and challenging roles: instructional manager; caring person; and, generous expert learner and cultural and civic person (Conway, Murphy, Rath, & Hall, 2009). Analysing the role of the teacher in six countries, Duda and Clifford-Amos Taking an international perspective, Townsend (2011) suggested that from the policy, research and practice points of view, ITE stakeholders are "on a quest" in an era of increasing accountability framed by conditions when:…”
Section: Reconsidering the Teacher Education Curriculummentioning
confidence: 99%
“…The need to restructuring ITE programmes in order to meet the demands of a more and more challenging profession and a changing society are also identified in the literature. However, changes in training programmes as a result of national and international policies have to be understood in the contexts in which they were produced (Flores, 2011;Townsend, 2011). Like other European countries, ITE in Portugal has been subject to a process of restructuring as a result of the Bologna process.…”
mentioning
confidence: 99%
“…With regard to the other initiative, the review of teacher education, it is noteworthy that professional educators were trusted to lead the enquiry and provide much of its data (Townsend 2011). Graham Donaldson's report, 'Teaching Scotland's Future' (Donaldson 2010) was accepted in full by the Scottish Government in March 2011, and over the next two years the 50 recommendations were fine-tuned by a group of 580 D. Gray and D. Weir stakeholders appointed by the government (National Partnership Group 2012), and their delivery is now supervised by a National Implementation Board and by the government.…”
Section: Partnershipmentioning
confidence: 99%